1957
DOI: 10.1063/1.1743267
|View full text |Cite|
|
Sign up to set email alerts
|

Displacement of the Maximum in the Concentration-Time Diagram of Uni-bi-, Bi-uni-, and Bi-bimolecular Consecutive Reactions

Abstract: As an extension of the results previously reported for two first-order consecutive reactions, the expressions k1·tmax and [B]max/[A]0 are studied as functions of temperature and initial parent concentration for uni-bi-, bi-uni-, and bi-bimolecular consecutive reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1969
1969
1996
1996

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Therefore, since the maximum concentration of the methyl radical may be calculated from the initial conditions of the experiment, both the absorption cross section and the rate coeficient for recombination may be determined in a single experiment. If the rate of dissociation of the precursor is comparable to the rate of recombination eq 1a becomes more complex, , but the above conclusion is still valid. If an alternate approach is used to produce the methyl radicals, for example a precursor with an unknown yield or simple photolysis, then it may not be possible to calculate the initial methyl concentration and eq 1a must be rewritten to give In experiments of this type, the cross section must be obtained from other measurements.…”
Section: Cross Section For Optical Absorptionmentioning
confidence: 93%
“…Therefore, since the maximum concentration of the methyl radical may be calculated from the initial conditions of the experiment, both the absorption cross section and the rate coeficient for recombination may be determined in a single experiment. If the rate of dissociation of the precursor is comparable to the rate of recombination eq 1a becomes more complex, , but the above conclusion is still valid. If an alternate approach is used to produce the methyl radicals, for example a precursor with an unknown yield or simple photolysis, then it may not be possible to calculate the initial methyl concentration and eq 1a must be rewritten to give In experiments of this type, the cross section must be obtained from other measurements.…”
Section: Cross Section For Optical Absorptionmentioning
confidence: 93%
“…Either of these cases would produce a kinetic system in which an irreversible second-order or pseudo second-order process follows an irreversible pseudo first-order process. TALAT-ERBEN (26) has shown that in such systems k~tma x decreases sharply and (B)max/(A)0 decreases gradually as (A)o is increased. Neither of these effects occurs at high pH', while the evidence for changes in kltma x or Emax/(A)0 at low pH' is marginal.…”
Section: Discussionmentioning
confidence: 99%